THE INFLUENCE OF INTELLECTUAL INTELLIGENCE, INTELLIGENCE SPIRITUAL AND EMOTIONAL INTELLIGENCE ON EMPLOYEE PERFORMANCE KENDARI NATIONAL SAR COMMUNITY - Ena Okta Saputri; Bakhtiar Abbas; Rince Tambunan (Maneggio, 2025)
The purpose of this study was to examine the influence of intellectual intelligence, spiritual intelligence, and emotional intelligence on the performance of Basarnas Kendari employees. The data analysis technique used multiple linear regression analysis with SPSS and data were collected through questionnaires from 70 employees. The results showed that these three intelligences together had a positive and significant effect on employee performance. The higher the intellectual, spiritual, and emotional intelligence of employees, the better their performance in carrying out rescue tasks. Intellectual intelligence has a positive effect on employees' ability to plan, analyze situations, and make the right decisions. Spiritual intelligence positively influences integrity, ethics, and composure under pressure. Meanwhile, emotional intelligence plays a crucial role in managing stress, building harmonious team relationships, and adapting to dynamic work situations, all of which increase employee effectiveness and efficiency.